Hypoxia-induced autophagy contributes to the chemoresistance of hepatocellular carcinoma cells - Song, Jianrui; Qu, Zengqiang; Guo, Xianling; Zhao, Qiudong; Zhao, Xue; Gao, Lu; Sun, Kai; Shen, Feng; Wu, Mengchao; Wei, Lixin (Autophagy, 2009)
Hypoxia commonly exists in solid tumors. In this adverse condition, adaptive responses including autophagy are usually provoked to promote cell survival. In our study, autophagy, a lysosomal-mediated degradation pathway, is demonstrated a protective way to make hepatocellular carcinoma cells be resistant to chemotherapy under hypoxia. Compared with normoxia, chemotherapeutic agents-induced cell death under hypoxia was significantly decreased, as a result of the reduced apoptosis. However, when autophagy was inhibited by 3-MA or siRNA targeted Beclin 1, this reduction was reversed i.e. chemoresistance was attenuated, which means autophagy mediates the chemoresistance under hypoxia. In conclusion, autophagy decreases hepatoma cells sensitization to chemotherapeutic agents by affecting their apoptotic potential.